2005
DOI: 10.1681/asn.2004030251
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch Induces Monocyte Chemoattractant Activity via an NF-κB-Dependent Monocyte Chemoattractant Protein-1-Mediated Pathway in Human Mesangial Cells

Abstract: Hemodynamic abnormalities are important in the pathogenesis of the glomerular damage in diabetes. Glomerular macrophage infiltration driven by the chemokine monocyte chemoattractant protein-1 (MCP-1) is an early event in diabetic nephropathy. The thiazolidinedione rosiglitazone ameliorates albumin excretion rate in diabetic patients with microalbuminuria and has anti-inflammatory properties, raising the possibility of a relationship between its renoprotective and anti-inflammatory activity. Investigated was wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 48 publications
4
71
0
2
Order By: Relevance
“…These data, indicating that NF-κB mediates MCP-1-induced TGF-β1 production, are in line with previous studies showing an NF-κB binding site in the TGF-β1 promoter region [29] and MCP-1-induced NF-κB activation in HMCs primed with IFN-γ [42]. Interestingly, we have recently shown that MCP-1 production in response to high glucose and stretch in HMCs is also mediated by an NF-κB-dependent mechanism [4]. The intracellular pathway mediating MCP-1/ CCR2-induced NF-κB activation remains undetermined; however, the signalling molecules phosphatidylinositol 3-kinase, Rho and janus kinase 2 are known to be activated by the MCP-1/CCR2 system [43][44][45] and can lead to NF-κB activation [46][47][48] in other cell types.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data, indicating that NF-κB mediates MCP-1-induced TGF-β1 production, are in line with previous studies showing an NF-κB binding site in the TGF-β1 promoter region [29] and MCP-1-induced NF-κB activation in HMCs primed with IFN-γ [42]. Interestingly, we have recently shown that MCP-1 production in response to high glucose and stretch in HMCs is also mediated by an NF-κB-dependent mechanism [4]. The intracellular pathway mediating MCP-1/ CCR2-induced NF-κB activation remains undetermined; however, the signalling molecules phosphatidylinositol 3-kinase, Rho and janus kinase 2 are known to be activated by the MCP-1/CCR2 system [43][44][45] and can lead to NF-κB activation [46][47][48] in other cell types.…”
Section: Discussionsupporting
confidence: 92%
“…Monocyte chemoattractant protein-1 (MCP-1) is a potent chemokine produced by activated monocytes and a variety of mesenchymal cells. In vitro, mesangial cell exposure to stretch and high glucose induces MCP-1 production resulting in monocyte chemotaxis [4]. In vivo, MCP-1 is overproduced in the glomeruli in experimental diabetes, an event paralleled by monocyte infiltration [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…43 These effects, which were further magnified by simultaneous exposure of mesangial cells to stretch and high glucose, were mediated by nuclear factor-kappa B (NF-kB). 44 Furthermore, both stretch and MCP-1 independently induce intercellular adhesion molecule-1 (ICAM-1) expression. 43 This would increase phagocytic leukocyte adhesion to mesangial cells 44 and amplify the inflammatory cascade 45 and may contribute to glomerular injury by inducing the release of cytotoxic reactive oxygen species.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 99%
“…44 Furthermore, both stretch and MCP-1 independently induce intercellular adhesion molecule-1 (ICAM-1) expression. 43 This would increase phagocytic leukocyte adhesion to mesangial cells 44 and amplify the inflammatory cascade 45 and may contribute to glomerular injury by inducing the release of cytotoxic reactive oxygen species. 46 Angiotensin II (Ang II), a powerful vasoconstrictor and trophic hormone, is central to renal damage in diabetes.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 99%
“…Mechanical stretch has been widely demonstrated as an inducer of cytokine synthesis in different tissues. 20,21 In particular, many have reported the ability of various uterine cell types such as fetal membrane epithelial cells, uterine myocytes and cervical fibroblasts to secrete cytokines following mechanical stretch stimulus. 22 Using murine models of gestation, we have demonstrated that rat and mouse myometrial smooth muscle cells (SMCs) are capable of producing multiple cytokines under the influence of uterine stretch imposed by the growing fetus around the time of labour.…”
Section: Introductionmentioning
confidence: 99%